Perbandingan Jenis-Jenis Agregat Kasar Batu Merak, Batu Hampangen dan Batu Banjar Untuk Campuran Beton Terhadap Kuat Tekan Beton Normal K-250 - ridwan ardiansyah (Universitas Muhammadiyah Surabaya, 2022)
The availability of local stone in Palangkaraya is very minimal, so the most of the chrushed stone in this region is came from other region. Coarse aggregates that can be found are merak stone, hampangen stone and pelaihari stone. The purpose of this study is to know the comparison of strength of the concrete produced by the coarse aggregate in the normal quality of K-250. Concrete mixture is using DoE (Departement of Enviroment) method. Three sample for each mixture. In this research, the design of the K-250 quality concrete mix was made with various types of different coarse aggregates, the concrete samples use the cube mold size 15cm × 15cm × 15cm, then the compressive strength test at age 7 days, 14 days and 28 days.The result of compressive strength test at age 28 days mixed merak stone concrete is 368,71 kg/cm2, mixed hampangen stone is 370,36 kg/cm2, and mixed pelaihari stone is 334,89 kg/cm2. The conclution is the concrete using of three coarse aggregates has a higher compressive strength than the planned quality. But the concrete using hampangen stone has the highest compressive strength.